MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PADA PEMBELAJARAN IPAS MENGGUNAKAN KOMBINASI MODEL PBL, NHT, DAN PICTURE AND PICTURE - Rahimah; Radiansyah (STKIP Subang, 2024)
The problem in this study is the low level of learning achievement, critical thinking, and learning activities. This happens because of the inappropriate way of learning, not being able to communicate well, not doing much learning that focuses on critical thinking, and only using the lecture method with printed materials. Combining PBL, NHT, and Picture and Picture models together will solve the problem. The purpose of this study was to describe teacher activities and analyze learner activities, critical thinking skills, and learning outcomes. A qualitative approach with the type of Classroom Action Research (PTK) for three meetings to complete. Based on qualitative data collected by observing what students and teachers do and how they think critically, quantitative data is used to determine learning outcomes. The research findings showed an increase in student activities, critical thinking skills, and learning outcomes. At each meeting, students' critical thinking skills improved to meet the requirements to be highly skilled in classical reasoning (90.48%), and their learning outcomes, both individually and in class, were able to meet the specified criteria (KKTP ≥75 with a percentage of 90.48%). The research findings support the idea that combining PBL, NHT, and Picture and Picture models with IPAS learning improves learners' learning outcomes and critical thinking skills.